(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this study, CuO thin films were deposited from the preparation of a gelatinous solution of aqueous copper acetate at a concentration of 0.6 M dissolved in 2-methoxyethanol, and mono ethanolamine was added to neutralize the pH of the solution to reach (Ph =7)) on glass bases and double-grafted with cadmium and cobalt in equal proportions